1988
DOI: 10.1093/oxfordjournals.ndt.a091693
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Interleukin-1 Production by Different Dialysis Membranes

Abstract: This study investigates the Il-1 production in vitro by normal peripheral blood monocytes or non-T cells following contact with different dialysis membranes (cuprophan, polysulphone, polymethylmethacrylate and polyacrylonitrile), in the presence or absence of lipopolysaccharide. The results of this study show that the physical contact between dialysis membranes and Il-1 producing cells is not by itself able to induce abundant Il-1 production unless exogenous lipopolysaccharide is added. A modest Il-1 productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Factors other than the membrane such as the device and the mode of therapy may account for the differences in predialytic levels of cytokines. The possible mechanism underlying the increased pro duction of IL-lp and TNF-a during the interdialytic period may be dependent on an endotoxin stimulation of monocytes/macrophages when endotoxin-containing dialysate diffuses back into the blood compartment, rather than on the interaction between dialy sis membranes and monocytes [19], Using an ELISA specific for antibodies to Escheri chia coli endotoxin and E. coli J-5 antigen, Yamagami et al [20] showed that hemodial ysis with high-flux, high-permeable mem branes is associated with the highest percent age of patients positive for endotoxin anti body as compared to that observed with lowflux membranes. Laude et al [21] have shown that lipopolysaccharide (LPS) may in deed cross polyacrylonitrile membranes at least in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Factors other than the membrane such as the device and the mode of therapy may account for the differences in predialytic levels of cytokines. The possible mechanism underlying the increased pro duction of IL-lp and TNF-a during the interdialytic period may be dependent on an endotoxin stimulation of monocytes/macrophages when endotoxin-containing dialysate diffuses back into the blood compartment, rather than on the interaction between dialy sis membranes and monocytes [19], Using an ELISA specific for antibodies to Escheri chia coli endotoxin and E. coli J-5 antigen, Yamagami et al [20] showed that hemodial ysis with high-flux, high-permeable mem branes is associated with the highest percent age of patients positive for endotoxin anti body as compared to that observed with lowflux membranes. Laude et al [21] have shown that lipopolysaccharide (LPS) may in deed cross polyacrylonitrile membranes at least in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This would be of particular importance when consid ering high-flux hemodialysis where endotoxin contami nation of dialysate is a significant clinical problem. Acti vation of lymphocytes and macrophages by dialysis membranes may further increase the production of cyto kines and their release into bone matrix and cartilage [44, [46][47][48]. The cytokines, TNFa and IL-1, exert a more powerful effect on bone resorption than parathormone, both in vitro and in vivo [44], In an exciting and unex pected development, Canalis et al [49] recently isolated a transforming growth factor from both bone matrix and calvarial cultures which they named bone-derived growth factor (BDGF).…”
Section: Cytokinesmentioning
confidence: 99%
“…Conflicting data exist about the specific effects of different membrane materials on cytokine release, especially with regard to so-called biocompatible and nonbiocompatible membrane types. While some authors found that complement-activating (nonbiocompatible) membranes led to a higher production of cytokines and their receptors than biocompatible membranes [13, 14, 15, 16, 17, 18], others found no such differences [19]or even opposite results [20, 21]. In one study, during short-term and long-term use, polyamide dialyzers were shown not to induce changes in plasma cytokine levels at all [22].…”
Section: Introductionmentioning
confidence: 99%